The Social Media and Reproductive Health Issues among Healthcare Practitioners in Jos, Plateau State, Nigeria - Lucas, Bernard Diesuk (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2025)
The Study assessed the use of social media to create awareness on reproductive health by Jos-based healthcare workers. It found that social media has become important in health discourse, especially as it concerns sharing health information on reproductive health by healthcare workers.